ASME 1997 Turbo Asia Conference 1997
DOI: 10.1115/97-aa-142
|View full text |Cite
|
Sign up to set email alerts
|

A New Gas Turbine Cycle for Economical Power Boosting

Abstract: A Moisture Air Turbine (MAT) cycle is proposed for improving the characteristics of land based gas turbine by injecting atomized water at inlet to compressor. The power boosting mechanism of MAT is understood as composits of those of following existing systems: inlet air cooling system, inter-cooling and steam injection. Experiments using a 15MW class axial flow load compressor have been carried out to reveal that water evaporation in compressor could reduce compressor work in an efficient manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Twin spool with power turbine RR Olympus performance boost by Utamura et al [16]. Wet compression allows the continuous evaporation during compression thus thermodynamically the compression is approaching the isothermal one resulting to a significant reduction of compressor specific work [19].…”
Section: Overspray Foggingmentioning
confidence: 98%
See 2 more Smart Citations
“…Twin spool with power turbine RR Olympus performance boost by Utamura et al [16]. Wet compression allows the continuous evaporation during compression thus thermodynamically the compression is approaching the isothermal one resulting to a significant reduction of compressor specific work [19].…”
Section: Overspray Foggingmentioning
confidence: 98%
“…Utamura et al [16] have reported a gain on thermal efficiency equal to 1.84% and on power equal to 8% for high humidity conditions and water injection of 0.65% mass flow fraction. The effect of 1% overspray on the performance of the Tornado engine calculated by the model is shown in Fig.…”
Section: Overspray Foggingmentioning
confidence: 99%
See 1 more Smart Citation
“…Deliberate compressor water injection, however, is substantially different. The most important difference is that for this approach, atomised droplets of typically small diameters (5-10m) are injected into the engine and have been observed to follow the flow path [8][9][10][11]. These droplets usually begin to evaporate in the initial/front stages of the compressor that brings about the cooling of the air flow (drop in temperature), increased density and moisture content.…”
mentioning
confidence: 99%
“…These droplets usually begin to evaporate in the initial/front stages of the compressor that brings about the cooling of the air flow (drop in temperature), increased density and moisture content. This procedure has been studied extensively through compressor analytical methods [11][12][13][14], through-flow approach, CFD approach [8,[15][16][17][18], and experimental investigations [9,[19][20][21] that have mostly focused on stationary gas turbines. For the analytical methods, Kim et al [22] categorise the models into: natural convection model, diffusion model and Stokes model.…”
mentioning
confidence: 99%